Food colloids interactions, microstructure and processing - Dickinson, Eric (Royal Society of Chemistry, 2005)
Food Colloids: Interactions, Microstructure and Processing describes the principles and practice underlying the formulation of food emulsions, dispersions, gels, and foams. Emphasis is on understanding how the functional properties of biopolymers and surfactants determine the texture and shelf-life of multiphase food materials. This book provides essential new findings by experts in the field on specific topics including: the interfacial rheological properties of proteins; the use of microscopy and image analysis to probe structure and phase transitions; the control of colloidal stability during thermal and mechanical processing; the interactions of proteins with polysaccharides and emulsifiers; the incorporation of neutraceuticals into food colloids; and the consumer perception of taste and texture. Food Colloids: Interactions, Microstructure and Processing provides a link between current research on the fundamental physical chemistry of colloidal systems and the requirements of the food technologist to use modern colloid science in new product formulation. It is suitable for postgraduates and researchers, both in industry and academia.
"The proceedings of Food Colloids 2004 : Interactions, Microstructure and Processing held on 18-21 April 2004 in Harrogate"--T.p. verso.
Keywords: Colloids -- Congresses.; Food -- Composition -- Congresses.; Food -- Analysis -- Congresses.; elektronické knihy; electronic books